RISK MANAGEMENT SUBSYSTEM OF THE AIS “REGION” - Райко, Галина Олександрівна; Данилець, Євген Валентинович; Карамушка, Марина Володимирівна; Соколова, Оксана Валентинівна (Eastern-European Journal of Enterprise Technologies, 2013)
The article is titled “The subsystem of risks management in the AIS (analysis information system) “Region”. The main topic of the article is the description of the AIS “Region” architecture that is oriented to the information support of making management decisions, analysis and forecasting of the socio-economic development of the region. The subject of investigation comprises the territorial and regional systems that are marked by high regularity and quantity of different interconnected subsystems, multi-loop control, hierarchy of the structures. The model of region, that represents the complex of the dynamic models formed on the balance base and joined together in the common network through the shared variables and thus creating the regional “balance of balances”, is described in the article. The article gives description of the analytical model of risk value function and its constants that must approximate the real empirical dependence of value from the risk in the field of determination. The application of situational forecasting methods, multiple statistical classification, capabilities of the computer data processing and multidimensional representation of results permits to visualize a large amount of information in a comprehensible way. The project management of regional development in the AIS “Region” involves not only the statement of fact of indeterminacy and risks, but also the analysis of risks and losses. Risk management subsystem includes the methods of analysis and neutralization of risk factors that are joined with the subsystems of planning, monitoring, DSS (decision support system).